2016
DOI: 10.1681/asn.2015080867
|View full text |Cite
|
Sign up to set email alerts
|

Serum Glucocorticoid–Regulated Kinase 1 Blocks CKD–Induced Muscle Wasting Via Inactivation of FoxO3a and Smad2/3

Abstract: Muscle proteolysis in CKD is stimulated when the ubiquitin-proteasome system is activated. Serum glucocorticoid-regulated kinase 1 (SGK-1) is involved in skeletal muscle homeostasis, but the role of this protein in CKDinduced muscle wasting is unknown. We found that, compared with muscles from healthy controls, muscles from patients and mice with CKD express low levels of SGK-1. In mice, SGK-1-knockout (SGK-1-KO) induced muscle loss that correlated with increased expression of ubiquitin E3 ligases known to fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 45 publications
(49 reference statements)
3
27
0
Order By: Relevance
“…In the cytosol, the increased GCs form complex with GR and then move to the nucleus for binding to the GC response element on the promoter of GR target genes (MSTN, KLF15, and FoxO3a) . They are well known to activate UPS through E3 ligase that degrades muscle proteins .…”
Section: Discussionmentioning
confidence: 99%
“…In the cytosol, the increased GCs form complex with GR and then move to the nucleus for binding to the GC response element on the promoter of GR target genes (MSTN, KLF15, and FoxO3a) . They are well known to activate UPS through E3 ligase that degrades muscle proteins .…”
Section: Discussionmentioning
confidence: 99%
“…FOXO3 has a relative molecular mass of ~71 kDa and contains five domains: a highly conserved forked-winged helix-turn-helix DnA binding domain (FKH), two nuclear localization sequences (nls), one nuclear export sequence and one c-terminal transactivation domain (tAD) (43). the highly conserved FKH domain primarily regulates the interaction between FOXO3 and DnA, and also mediates its interaction with estrogen receptor α (44) and tumor protein p53 (p53) protein (45). the translocation of FOXO3 from the cytoplasm to the nucleus requires the nls domain, which mediates the release of FOXO3 from the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…FOXO3 is phosphorylated by upstream kinases such as AKt, erK, serum/glucocorticoid regulated kinase 1, inhibitor of nuclear factor-κB kinase subunit β and inhibitor of nuclear factor-κB kinase subunit ε. the dysregulation of these kinases often occurs in different types of cancer and facilitates tumor progression by promoting the FOXO nuclear-cytoplasmic shuttle or ubiquitin-dependent protein kinase degradation (46)(47)(48)(49). the carcinogenic effects of FOXO3 dysfunction are mediated by a variety of mechanisms that involve several genes associated with apoptosis, such as Bim, noxa, Puma, Fasl and trAIl, in addition to genes controlling cell proliferation, such as p21, p27, p130, cyclin g2 and gADD45 (45). therefore, the increased expression of the FOXO3 gene is associated with the incidence of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, CKD had the opposite effect. Previous studies demonstrated that exercise training efficiently attenuated CKD-induced muscle atrophy by suppressing MAFbx and MuRF1 transcription 42 , 43 . Of interest is that a pan-WNK kinase inhibitor WNK463 increased atrogene transcription in mouse skeletal muscle and C2C12 cells (Fig.…”
Section: Discussionmentioning
confidence: 98%